The effect of haemolysis on the direct and indirect ion selective electrode measurement of sodium. (May 2021) - Kalaria, Tejas; Gill, Henry; Harris, Steve; Ford, Clare; Gama, Rousseau
Background: We compared the effect of haemolysis in sodium measurement using indirect and direct ion-selective electrodes to test the hypothesis that haemolytic effect on sodium would be greater with indirect ion-selective electrode due to electrolyte exclusion effect from released intracellular proteins. Methods: Plasma lithium heparin samples ( n  = 36) from four volunteers were prepared to give a range of haemolytic indices (H-indices). Samples were analysed for sodium by indirect ion-selective electrode, H-index and total protein on an Abbott Architect c16000 and sodium by direct ion-selective electrode on a Siemens RAPIDPoint 500. Percentage changes in sodium in paired direct and indirect ion-selective electrode values were compared. Results: Abbott H-index, which represents haemoglobin concentration in g/L, correlated with percentage negative change in sodium by direct ion-selective electrode (ρ 0.995, P  < 0.001) and indirect ion-selective electrode (ρ 0.991, P  < 0.001). Percentage negative change was less when sodium was measured by direct ion-selective electrode compared to indirect ion-selective electrode (Wilcoxon signed-rank Z = 3.46, P  = 0.01). The difference in percentage change in sodium between direct ion-selective electrode and indirect ion-selective electrode correlated with total protein (ρ 0.751, P  < 0.001). The negative bias in sodium results exceeded the reference change value of 2.2% at an H-index of 8.31 for indirect ion-selective electrode and 9.26 for direct ion-selective electrode. Conclusion: Haemolysis causes negative influence with sodium measured by both indirect and direct ion-selective electrode due to a dilutional hyponatremia. The additional interference in indirect ion-selective electrode is due to the electrolyte exclusion effect but this is unlikely to be clinically significant as it is small in magnitude.